Problematyka badawcza teologii dogmatycznej w „Collectanea Theologica” 1920-2020 - Bachanek, Grzegorz (Collectanea Theologica, 2020)
The following research areas of dogmatic theology were developed in the publications that appear in “Collectanea Theologica”: the theology of the Divine Mercy, the reflection on time which enriched Christology, the anthropological expression of Marian theology, the concept of personalism as a possible way of theological renewal, and Christian solidarity. Theologians proposed the hypothesis of the baptism of the Church, the theology of the icon, and the concept of a universal Eucharist. Among other questions they discussed the notion of the suffering of God. We can also find an original expression of theology of space, human freedom, and the theology of rest as well as a valuable perspective on the charisma of the theologian. Already in the interwar period, the journal was a place of encounter between the theology of the Christian West and that of the East. Some dogmatists, who published the results of their research in the journal, made the effort of confronting the theological topics with the problems and solutions from other branches of scholarship. Attempts were undertaken to explore thoroughly and interpret specific Christian elements in literature. History was treated as a dynamic reality and a source of inspiration for the contemporary world. The Second Vatican Council had a profound influence on the publications, as it provided a challenge to the adequately understood renewal of Catholic theology.